(untitled) (The Strategic Review for Southern Africa, 2021)
At the heart of the conundrum of regional integration in Africa is the very conceptual basis of the idea and its agendas. In southern Africa, the agenda has for decades been about fighting poverty and enabling a good life for the citizens of the region, but the so-called developmental regional integration agenda is undermined by the lack of coherence and synergy between the security and development arms of the Southern African Development Community (SADC). The former has the Strategic Indicative Plan of the Organ of Security Cooperation and Defence (SIPO) and the development efforts are guided by the Regional Indicative Strategic Development Plan (RISDP). Both claim to pursue human security by placing the plight of ordinary citizens at the centre of all efforts, yet in reality this shared aspiration has not provided a basis conceptually speaking, nor practically, for a deep cohesion in the manner in which SADC pursues its overriding goals. This article provides a critical analysis of the evolution of the concept and it also anticipates how it will evolve into a holistic idea in southern Africa. It identifies major obstacles to the achievement of the goal and offers possible solutions to the conceptual confusion that confounds the idea of human security by suggesting a comprehensive understanding of the concept and how it might apply in southern Africa.